In Vitro Production of Ovine Embryo in Non-Breeding Season - A. A. Omar1 , M. N. Ahmed2 , Audai Sabah Asker3 , A. F. Majeed1 , T.M. Faraj4 , S.J. Rejah4 (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study was undertaken to show the effect of follicular size and culture media on the results of IVFand IVEP in sheep. A hundred ovaries of slaughtered ewes were taken during non-breeding season. Thetotal number of follicles were 256, while the number of recovered oocytes were 189. The recovery rateof oocyte from large and small follicles were 85.8% and 64.7% respectively. Only grades A and B oocytehave been used with a total number of 148 oocytes. Maturation and fertilization rates in different media;MEM, RPMI1640, DMEM low glucose and DMEM high glucose were 64.4%, 51.2%, 32.4% and 26.6% formaturation rate and 66.6%, 55%, 50% and 37.5% for fertilization rate respectively. There was a statisticaldifference (p?0.05) in maturation and fertilization rate between different media; the total fertilization andcleavage rate was 56.7% and 70% respectively. The numbers of morula and blastocyst stage were 40% and35% respectively. There was a statistical difference (p?0.05) in morula and blastocyst production in differentmedia. It was concluded that abattoir was a good source of oocyte recovery, and the large follicle give thebest morula and blastocyst stage. MEM was a good diluent of semen. mMEM give the best result as culturedmedia as compared with the other media used in this study.